Pharmacological effect of synobiotic and phytobiotic in kidney function and some blood parameters of chicken - Kamel O. I., Marwa; A. A. El-Komy, Ashraf; A. A. Farag, Enas (International Journal of Pharmacology and Toxicology, 2021)
The aim of this research was to study the effects of dietary supplementation of â€Žsynbiotic, phytobiotics and their mixture on kidney functions, some blood parameters and histological criteria of broilers. A total of 200 â€Žbroiler chicks were randomly chosen and divided into eight groups (25 birds in each). The first four groups were unvaccinated chicken which received a basal diet (group 1) or â€Žthe same diet supplemented with 1g synobiotic /kg body weight (group 2), 1g phytobiotic /kg body weight (group 3) and 1g â€Žsynobiotic plus 1g phytobiotic/kg body weight (group 4). The second four groups were vaccinated chicken and fed the same previous treatments with groups 5, 6, 7 and 8, respectively. Therapeutic dose of synobiotic and phytobiotic or their mixture (1ml/ kg. body weight) orally for 3 â€Žsuccessive days â€Žtended to decrease uric acid and creatinine in unvaccinated and vaccinated chicken at 7, 14 and 21 day. In this study uric acid and â€Žcreatinine levels resulted in decrease, showing a significant improvement of kidney functionsâ€Ž â€Ž. Some different parameters of blood and histological criteria showed normal measurements with no adverse effect of treatments.Â Â Â